Analisis Potensi Ekonomi Dan Kependudukan Dalam Pertumbuhan Ekonomi Di Kabupaten Mamuju Provinsi Sulawesi Barat - Tityas Margawati (Akuntansi & Ekonomika, 2022)
To increase the rate of economic growth of a region, it is necessary to assess the economic sector owned which is progressing every year. The purpose of this research on population economics in Mamuju is to identify potentials and see growth trends in each economic sector in Mamuju. The method used is analysis of Location Quotients (LQ) and Shift Share. The economic sector is linked to population dynamics to see the relationship between regional economy and population dynamics in Mamuju as a material for determining development planning strategies in the economic sector. Of the 17 existing sectors, there are 13 sectors which are the base sector and are progressing in contributing to the value of PDRB. From these results and supported by the dynamics of the increasing population, Mamuju Regency needs to increase the contribution of the sector to meet the needs of residents inside and outside Mamuju Regency.